ChemInform Abstract: Surface Science Approaches for the Preparation of Alumina‐Supported Hydrotreating Catalysts. Issue 51 (December 2015) - Bara, Cedric; Devers, Elodie; Digne, Mathieu; Lamic‐Humblot, Anne‐Felicie; Pirngruber, Gerhard D.; Carrier, Xavier
Abstract: Review: 158 refs.